2018
DOI: 10.3389/fsufs.2018.00086
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Salmonella enterica Outbreaks in Australia, 2001–2016

Abstract: Salmonella enterica is an important cause of foodborne illness in Australia, regularly causing high-profile outbreaks involving commercially-available foods. We used the national register of foodborne outbreaks to review the transmission pathways, settings, serotypes, and food vehicles of Salmonella outbreaks in Australia between 2001 and 2016. We examined trends over time of implicated food vehicles in outbreaks where there was statistical, microbiological, or descriptive evidence. Of the 990 Salmonella outbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 14 publications
0
35
1
Order By: Relevance
“…The majority (84%) of reported foodborne Salmonella spp. outbreaks in Australia between 2001 and 2016 were attributed to S. Typhimurium, while only 1% of these outbreaks were related to S. Infantis [32]. Although human cases associated with S. Infantis are not as common as those associated with S. Typhimurium, S. Infantis has emerged as the fourth most common serovar causing human salmonellosis in Europe in 2014 [33].…”
Section: Diversity Of Salmonella Subtypes Recovered From Environmentamentioning
confidence: 99%
“…The majority (84%) of reported foodborne Salmonella spp. outbreaks in Australia between 2001 and 2016 were attributed to S. Typhimurium, while only 1% of these outbreaks were related to S. Infantis [32]. Although human cases associated with S. Infantis are not as common as those associated with S. Typhimurium, S. Infantis has emerged as the fourth most common serovar causing human salmonellosis in Europe in 2014 [33].…”
Section: Diversity Of Salmonella Subtypes Recovered From Environmentamentioning
confidence: 99%
“…Despite the high incidence and case numbers, Campylobacter outbreaks remain less frequently reported in Australia (Unicomb et al, 2009;Moffatt et al, 2017a). This contrasts markedly with Salmonella enterica, another enteric pathogen of public health significance, responsible for *1000 outbreaks in Australia between 2001(Ford et al, 2018. Nevertheless, outbreak data contribute to our understanding of Campylobacter's epidemiology, showing food vehicles such as poultry-liver pâté have become an established cause of outbreaks internationally (Little et al, 2010;Lanier et al, 2018).…”
mentioning
confidence: 99%
“…Microbiological analysis showed that 67.7% of samples in the current study were negative for all investigated bacteria; from a minority (4.4%) though Salmonella Typhimurium was isolated. This serovar in turn is among the most prevalent causing gastroenteritis in humans (FERNANDES et al, 2006;EFSA-ECDC, 2017), and outbreaks related to RTE foods, including salami, have been reported (COWDEN et al, 1989;CDC, 2018;FORD et al, 2018). In Brazil, there are relatively little epidemiological data on Salmonella outbreaks (TAVECHIO et al, 2002;GEIMBA et al, 2004), although this pathogen ranks first in terms of official data (BRASIL, 2016).…”
Section: Discussionmentioning
confidence: 99%